Developing regulatory standards for the concept of security in online dispute resolution systems. Issue 5 (October 2019) - Abedi, Fahimeh; Zeleznikow, John; Brien, Chris
Abstract: Online dispute resolution (ODR) has improved access to justice in the digital world. ODR users benefit from faster and cheaper dispute resolution mechanisms compared to traditional litigation and Alternative Dispute Resolution. There are few and quite varied regulatory systems for ODR. This research aims to develop a set of standards to measure the concept of security and to increase the consistency of security in ODR systems. An exploratory mixed method approach is used, involving a quantitative (survey) and mainly qualitative approach (face-to-face interviews) for gathering data. We identify three elements of information security, privacy, and authentication as standards for an appropriate ODR legal framework. Finally, these findings led to practical implications for policy makers and regulators.